Pemanfaatan Aplikasi Quizizz Sebagai Solusi Pembelajaran Menyenangkan di Tengah Pandemi Pada Siswa Sekolah Dasar - Aldanisa Eka Iswantari Putri; Frestiuli Meysanti; Shofiyatul Husna (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
The covid-19 pandemic government offers policies on the education sector of learning systems at any level of education. It is accompanied by debriefing applications of remote learning or online learning. To make it easier for online learning, relevant, interesting and fun media needs for elementary school students. Using a truly innovative quizizz application, it is hoped that learners can learn more inventive and thus make learning more enjoyable. The study used literature study methods by reading, studying, and reviewing books or writings related to the study and while attending college teaching programs. Based on research of achievable results in the quizziz application asa learning medium, namely: (1) the quizizz application may evaluate students independently. (2) the results of learning can be seen in person. (3) makes the process of online learning more varied and more efficient. (4) quizziz application only to know students' abilities in cognitive domains.